GAYA KOMUNIKASI SELEGRAM PEREMPUAN MAKASSAR (PEMBENTUKAN CITRA DIRI) - Suparman; Rahmawati Latief; Andi Fauziah Astrid (Jurnal Kajian Ilmu Komunikasi, 2021)
This study is to determine the communication style used by the Makassar women's celebrity instagram in shaping self-image. This study also explores the supporting and inhibiting factors of the Makassar women's celebrity Instagram communication style in forming self-image. The results of this study indicate that the female celebrity Instagram communication style Makassar uses The Dynamic Style communication style with a self-image as a positive person. The controlling style by building self-image as an outgoing and cheerful person. The Equalitarian Style of communication is known as a simple and friendly celebrity Instagram. Supporting factors in communication such as physical, historical, and related conditions have an influence on each informant. Role and historical factors, language factors, as well as content or discussion. Each informant considered that the communication facilities were good enough and did not feel the impact of the communication equipment barriers. To prevent semantic obstacles, each informant is very careful in uploading a photo or video on their Instagram account. In addition, a celebrity tries to find out the character of his followers to avoid misunderstanding from the different backgrounds of his followers